Artificial human nature. - Sack, Warren (Design Issues)
Presents arguments on artificial intelligence (AI) design critics' blindness to the cultural and ethical implications of artificial intelligence. AI critics' preoccupation with the identification of the essentials of human nature; Contentions that design work should complement the `natural.'